The effect of ageing and physical activity level on muscle fatigue during isometric contraction of knee extensor muscles - Nahar, Nazmun (2013)
Nahar, Nazmun 2013. Effect of ageing and physical activity level on muscle fatigue during isometric contraction of knee extensor muscles. Master’s theses in Biomechanics. Department of Biology of Physical Activity, University of Jyväskylä, Finland.